18PClinical outcome of personalised treatment guided by genome and transcriptome sequencing in patients with neuroendocrine neoplasms: Updated results from the German NCT/DKTK MASTER trial. (7th November 2019) - Kreutzfeldt, S; Apostolidis, L; Oles, M; Horak, P; Heilig, C E; Heining, C; Hutter, B; Klink, B; Lamping, M; Uhrig, S; Stenzinger, A; Winkler, E C; et al.
Abstract: Background: Therapeutic options for neuroendocrine neoplasms (NEN) are limited, and only few NEN patients have been treated according to their individual genomic profile. We report the molecular and clinical characteristics of a large NEN cohort that was studied by prospective whole-genome (WGS), whole-exome (WES), and transcriptome sequencing (TS) within the NCT/DKTK MASTER precision oncology program. Methods: Between 2013 and 2018, a total of 115 patients with advanced, heavily pretreated NEN were enrolled. Primary sites were gastrointestinal (n = 30), pancreatic/hepatic (n = 33), pulmonary (n = 20), genitourinary (n = 13), head/neck (n = 6), and other regions (n = 11). Grading according to the 2017 and 2019 WHO classification was neuroendocrine tumor (NET) G1, n = 12; NET G2, n = 31; NET G3, n = 12; neuroendocrine carcinoma, n = 36; mixed neuroendocrine-non-neuroendocrine neoplasm, n = 12; and other, n = 11. Results: Of WES (n = 72) or WGS (n = 44) and TS (n = 92) were discussed in a multidisciplinary molecular tumor board. Recommendations were given in 103 cases (94%) for the following potential treatment alternatives: tyrosine or serine/threonine kinase inhibition (n = 67), PARP inhibition (n = 41), immunotherapy (n = 33), mTOR inhibition (n = 30), CDK4/6 inhibition (n = 19), MEK inhibition (n = 12), platinum-based chemotherapy (n = 7), BET inhibition (n = 7), anti-claudin18.2 (n = 5) or anti-DLL3 antibody treatment (n = 8). Somatic hypermutation (>10 mutations/megabase) was seen in 8.6% of patients. Treatment options could be implemented in 35 patients, of which 31 were evaluable for response: partial response, n = 10; mixed response, n = 1; stable disease, n = 11; progressive disease, n = 9; resulting in an overall response rate of 32% and a disease control rate of 71%. Conclusions: Comprehensive genomic and transcriptomic characterization provides new insight into the molecular pathogenesis of NEN and creates therapeutic opportunities in a significant proportion of NEN patients who have exhausted standard treatment. Legal entity responsible for the study: NCT Heidelberg & German Cancer Consortium. Funding: German Cancer Research Center. Disclosure: S. Kreutzfeldt: Research grant / Funding (institution), Travel / Accommodation / Expenses: PharmaMar; Honoraria (self): Novartis; Research grant / Funding (institution): Roche; Travel / Accommodation / Expenses: Pfizer. C.E. Heilig: Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: PharmaMar; Honoraria (institution), Travel / Accommodation / Expenses: Lilly; Travel / Accommodation / Expenses: Novartis; Travel / Accommodation / Expenses: Celgene; Travel / Accommodation / Expenses: Teva; Travel / Accommodation / Expenses: BMS; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Pfizer. All other authors have declared no conflicts of interest.